DERMOPREPARATIONS WITH ANTIACNEIC ACTION. FORMULATION AND PHARMACOTECHNICAL EVALUATION - Gabi Topor; Olimpia Dumitriu Buzia; Riana Maria Huzum; Mălina Iris Maftei; Dinu Monica; Cristina Serban (Romanian Society of Oral Rehabilitation, 2024)
The present work aimed to create and evaluate some topical pharmaceutical forms with a role in the improvement and treatment of acne. Also, the work aims to characterize the pharmaceutical forms obtained from the point of view of efficiency by determining some physico-chemical and pharmaceutical parameters. The purpose of these determinations is to specify some important aspects with a role in prevention and avoiding recidivism. We created two different pharmaceutical forms, using two concentrations of antibiotic and keratolytic agent, namely, a solution with erythromycin 4% and resorcinol 1% and two creams with erythromycin 1.2% and resorcinol 2% in different emulsion U type ointment bases /A and A/U used in the treatment of acne depending on its stage. Our study followed the macroscopic evaluation of the pharmaceutical forms made, the ph over a period of 30 days, the influence of the ointment bases on the rheological behavior, the satisfaction of the complexity of the treatment on different forms of acne. Microbial contamination is also a quality parameter and was evaluated to observe the behavior of excipients as possible microbial culture media